Heart failure as a risk factor of adverse drug reactions. Part 1: potential changes in pharmacokinetics - Pereverzev, A. P.; Ostroumova, O. D. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2022)
The use of many drugs is associated with the risk of adverse drug reactions (ADRs), including those that increase mortality and / or morbidity and / or seek medical help or hospitalization, so called «drug-induced diseases» (DID). There is a number of factors that increase the risk of DID (risk factors) including comorbid diseases (for example, chronic kidney disease, hepatic impairment, obesity etc.). These pathologic conditions induce changes in pharmacokinetics (PK) and pharmacodynamics of drugs, thereby increasing the risk of ADRs. One of these diseases is heart failure (HF). Most studies of PK changes were conducted among patients with LVEF from 40 to 45 %, and excluded patients with concomitant diseases that could affect the PK of drugs (for example, serious liver and / or kidney diseases), therefore in polymorbid patients, trial findings may not be applicable. HF may be associated with a decrease in bioavailability, a decrease in volume of distribution, a change in the activity of cytochrome P450 isoenzymes, etc. Individual dose and dosage regimen adjustment can significantly reduce risks, improve the quality of medical care and improve the prognosis in patients with heart failure.